1998
DOI: 10.1097/00001756-199804200-00018
|View full text |Cite
|
Sign up to set email alerts
|

Expression of an oscillating interferon-γ receptor in the suprachiasmatic nuclei

Abstract: The suprachiasmatic nuclei serve as the dominant circadian pacemaker in the mammalian brain, regulating daily behavioral, physiological and hormonal rhythms. In the ventrolateral parts of these nuclei, the receptor for the key immunoregulatory molecule interferon-gamma (IFN-gamma) was detected in the rat brain. The cellular localization of the IFN-gamma receptor corresponded to neuronal elements. Expression of the receptor followed a diurnal rhythm with a peak at zeitgeber time 15. This peak coincided with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 8 publications
0
30
0
1
Order By: Relevance
“…In this sense, Nishiuchi et al [31] showed that there were no differences in tissue distribution after murine recombinant IFN-gamma administration in mice, rats or hamsters, suggesting an absence of species specificity between them. The finding that the IFN-gamma receptor is expressed in the SCN [24,32] suggests that the effects seen could be exerted directly by IFN-gamma in the SCN. However, another hypothesis cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, Nishiuchi et al [31] showed that there were no differences in tissue distribution after murine recombinant IFN-gamma administration in mice, rats or hamsters, suggesting an absence of species specificity between them. The finding that the IFN-gamma receptor is expressed in the SCN [24,32] suggests that the effects seen could be exerted directly by IFN-gamma in the SCN. However, another hypothesis cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…A light-dependent immunopositivity for the IFN-gamma receptor is detectable in the SCN, its expression displaying a daily rhythm with a peak at Zeitgeber time (ZT) 15 (with ZT 12 defined arbitrarily as the time of lights off) [24]. Furthermore, in rats the locomotor activity and rearing were reduced following central administration of IFNgamma even 7 days after injection [25].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, IFN-Á could modify the activity of sympathetic nerves, which, in turn, would modulate LPS or Con A responses. In addition, there is indication on the expression of an oscillating IFN-Á receptor in the ventrolateral parts of the suprachiasmatic nuclei, the major circadian oscillator in the CNS, supporting the view that the pacemaker of the biological clock can be influenced by the cytokine [67].…”
Section: Local Sympathectomy Influences Specific Responses In Immune mentioning
confidence: 75%
“…Accumulating evidence demonstrates that a decreased Th1 immune response is also important in the pathogenesis of allergic diseases, and that interferon-γ (IFN-γ) could act as a central regulator in this phenomenon [32]. On the other hand, a light-dependent immunopositivity for the IFN-γ receptor is detectable in the SCN [33]. Accordingly, Th1/Th2 balance-related cytokines, such as IFN-γ, might thus be associated with the outcome.…”
Section: Discussionmentioning
confidence: 99%